Preparation and Characterization of EVAc/ TiO2 Nanocomposites Coating for Oil Pipes Protection - Aldabbagh, Balqees M.; Kadhim, Hanaa Jawad (Journal of Petroleum Research and Studies, 2024)
The spin coating process was used in this study to create nanocomposites of ethynevinyl acetate copolymer reinforced with nano titania nanoparticles at various ratios (50, 100, & 150 part/million). Using Fourier-transform infrared spectroscopy (FTIR), different types of reactions between TiO2 and EVAc were investigated. Deferential Scanning Calorimetry was used to study melting point of thin films. As well as , anti corrosion resistance of thin films using electrochemical method were studied Results show that the adding of TiO2 nanoparticles enhanced the thermal characteristics of nano composite thin films, Tm increasing from 66 oC to 71 oC, The results of the FTIR analysis demonstrate that the nanoscale TiO2 and EVAc are physically reacting. Anti-corrosion behavior shows that the corrosion current reduces from 188 mA to 1 nA and corrosion resistance was increased. Additionally, the efficacy of inhibition increased from 0.0 to 99%. with adding Nano TiO2 with 150 ppm to thin films.